Astrocytic heterogeneous nuclear ribonucleoprotein U is involved in scar formation after spinal cord injury - Lili Quan; Akiko Uyeda; Ichiro Manabe; Rieko Muramatsu (Journal of Neuroinflammation)
Abstract Astrocytes have a beneficial role in tissue repair after central nervous system (CNS) injury. Although astrocyte proliferation is activated in response to injury, the intracellular mechanisms of astrocyte proliferation during acute phase of injury are not fully clarified. In this study, by functionally screening the highly expressed genes in the pathological state of spinal astrocytes, heterogeneous nuclear ribonucleoprotein U (Hnrnpu) is identified as a potential endogenous molecule that regulates astrocyte proliferation and the following scar formation. Inhibition of Hnrnpu in astrocytes impairs the formation of astrocytic glial scar, motor function recovery, and neuronal regeneration after spinal cord injury (SCI) in mice. In human astrocytes, HNRNPU knockdown downregulates the genes related to the astrocyte functions in scar formation and neuronal regeneration. These findings uncover that modulation of endogenous astrocytic function would be a promising therapeutic avenue to restore neurological function after CNS injury.